Peningkatan perawatan transisi yang sebagai strategi untuk mengurangi penerimaan kembali pada pasien stroke: Sebuah tinjauan sistematis - Septianingrum, Yurike; Nurjanah, Siti; Nursalam, Nursalam (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2022)
Introduction: Transitional Care (TC) was developed to reduce hospital readmission and improve the physical ability of stroke patients. The purpose of this literature review is to identify the application of Transcultural Care to the readmission rate in stroke patients. Method: Article searches were conducted using the same keywords in the Pubmed, CINAHL, SAGE and Science Direct databases published from January 2016 to September 28, 2021. A total of eight articles were identified in this study. Results: Eight articles were reviewed regarding the results of applying TC to the readmission rate in stroke patients. All reviewed articles showed a decrease in the readmission rate after TC was applied compared to usual care. There was substantive heterogeneity in (1) TC team coordinator, (2) hospital/clinic to home TC process, (3) TC follow-up duration, (4) satisfaction. Conclusions: Several articles support the positive results of using TC on readmission rate before 30 days and satisfaction with nursing services in patients with stroke. Standardization of interventions and research designs are needed to determine the most effective interventions.